Functional MRI with a set-shifting task in adolescent anorexia nervosa: A cross-sectional and follow-up study. (August 2019) - Castro-Fornieles, Josefina; Serna, Elena de la; Calvo, Anna; Blázquez, Anna; Moya, Jaime; Lázaro, Luisa; Andrés-Perpiñá, Susana; Plana, María Teresa; Gil, Laia; Flamarique, Itziar; Martínez, Esteve; Pariente, Jose; et al.
Abstract: Studies of set-shifting in adolescent AN present conflicting results, since not all have found differences with regard to controls. To date, no functional Magnetic Resonance Imaging (fMRI) studies have been carried out in adolescent patients, nor have patients been assessed after weight recovery. In this study, 30 female AN patients aged 12–17 and 16 matched control subjects were assessed both at baseline and after six months and renutrition using a structured diagnostic interview, clinical and neurocognitive scales, and fMRI during a set-shifting task. Adolescent AN patients presented similar performance on different neurocognitive tests and also on a set-shifting task during fMRI, but they showed a lower activation in the inferior and middle occipital and lingual gyri, fusiform gyri and cerebellum during the set-shifting task. No correlations were found between decreased activation and clinical variables such as body mass index, eating or depressive symptoms. After six months of treatment and renutrition in AN patients, there were no differences between patients and controls. These results show that adolescent AN patients have lower activation in relevant brain areas during a set-shifting task, and support the use of fMRI with set-shifting paradigms as a biomarker in future studies. Highlights: Adolescent AN patients showed a lower activation in some brain areas during the set-shifting task. No correlations were found between decreased activation and clinical variables. After six months of treatment there were no differences between AN patients and controls.